The Analysis of Regional Tax Revenue in Increasing Regional Original income (PAD) of Deli Serdang - Devi Purnama Sari (Institute of Computer Science (IOCS), 2022)
Regional Tax is the contribution of Regional Taxpayers owed by individuals or entities that are compelled by law, without getting a direct imbalance and are used for regional needs for the greatest prosperity of the people. Local tax collection is used to finance the government and increase local revenue. The purpose of this study was to analyze the Regional Tax Revenue of Deli Serdang Regency in increasing the Regional Original Income (PAD) of Deli Serdang Regency. The type of research conducted in this research is descriptive quantitative. This research was conducted with time series data from 2017-2021. This study uses secondary data sourced from the Financial and Asset Management Agency of Deli Serdang Regency and the Central Statistics Agency. The results of this study indicate that the Regional Tax of Deli Serdang Regency can increase the Regional Original Income of Deli Serdang Regency. It can be seen that every year from 2017 to 2021 the Regional Tax revenue of Deli Serdang Regency can contribute between 65.18% to 79.06% of Deli Serdang Regency's Original Revenue.